2020
DOI: 10.3390/min10010064
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Inclusion Characteristics of the Kışladağ Porphyry Au Deposit, Western Turkey

Abstract: The deposit occurs in a mid-Miocene monzonite magmatic complex represented by three different intrusions, namely Intrusion 1 (INT#1), Intrusion 2 (INT#2, INT #2A), and Intrusion 3 (INT#3). Gold mineralization is hosted in all intrusions, but INT#1 is the best mineralized body followed by INT#2. SEM-CL imaging has identified two different veins (V1 and V2) and four distinct generations of quartz formation in the different intrusions. These are: (i) CL-light gray, mosaic-equigranular quartz (Q1), (ii) CL-gray or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In conclusion, the chemical data of tourmalines from the Kışladag gold deposit has helped in understanding its formation during various alteration/mineralizing (potassic/propylitic), phyllic and argillic stages in a telescoped porphyry/epithermal system. The data is consistent with the fluid inclusion data for Kışladag deposit [13] that supported the process of an epithermal overprint of the porphyry mineralization.…”
Section: Intrusions #2 and #3 (Int#2 And Int#3)supporting
confidence: 87%
See 4 more Smart Citations
“…In conclusion, the chemical data of tourmalines from the Kışladag gold deposit has helped in understanding its formation during various alteration/mineralizing (potassic/propylitic), phyllic and argillic stages in a telescoped porphyry/epithermal system. The data is consistent with the fluid inclusion data for Kışladag deposit [13] that supported the process of an epithermal overprint of the porphyry mineralization.…”
Section: Intrusions #2 and #3 (Int#2 And Int#3)supporting
confidence: 87%
“…The Biely Vrch tourmaline crystallized from an unusual Cl-rich high-temperature fluid [38], whereas tourmaline from the sandstone cement in Poland was related to the low-temperature diagenesis of evaporite sediments inducing reactions of quartz and clay minerals [39]. The fluid inclusion study at the Kısladag deposit [13] revealed a high-temperature, highly saline fluid was responsible for the formation of most of the gold-bearing veins. It can be ruled out that this fluid was released from fluid inclusions during the late epithermal overprint and incorporated into the Cl-rich tourmaline.…”
Section: Intrusions #2 and #3 (Int#2 And Int#3)mentioning
confidence: 99%
See 3 more Smart Citations